Nutritive value of forages as affected by soil and climatic differences. - Koch, B.A.; Smith, E.F.; Richardson, D.; Cox, R.F.; Ordoveza, A. (Kansas Agricultural Experiment Station, 2011)
There has long been evidence that forages produced on different types of soil in the same general area give significantly different results when fed to animals. Further information is needed on the composition and nutritive value of forages grown on soils differing in origin, fertility, and other characteristics. This is a progress report of the wintering phase of the first trial in this study. The study has been designed to measure differences in the results obtained when cattle are grazed on forages growing on limestone or sandstone soils.
Keywords: Beef; Nutrition; Forage; Soil; Climate